Revisão do complexo ophioscion punctatissimus meek & Hildebrand, 1925 (Actinopterygii: sciaenidae) - Santos, Jonas de Andrade (2022)
Sciaenidae are a speciose fish family in the marine environment, its members are well-known by their sound production and morphological specializations in the sensory system such as their relatively big otoliths (i.e., inert structure of the inner ear), and cephalic lateral line system. In Stelliferinae, the lower phenotypic disparity has led to taxonomic uncertainties. The genus Stellifer and Ophioscion are recognized as non-monophyletic; herein, we recognize that Ophioscion Gill, 1863 is a junior synonym of Stellifer Oken, 1817. The genus is distinguished from the other genera in Stelliferinae by their vertebral counts (10 + 15) and the enlarged lapillus; which is almost the same size of the oval shaped sagittal otoliths. The complex Stellifer punctatissimus is one of these examples of uncertainties; it was initially recognized on a morphological basis as presenting putatively two other species. However, this morphological hypothesis was not confirmed by molecular data, that suggested that occurs only two evolutionary lineages in this species complex. Thus, we tested herein the morphological hypothesis of three species on the complex by using linear and geometric morphometrics in the body shape. In addition, shape indices, Fourier descriptors and geometric morphometrics in the shape and outline of the otoliths were used. An overlapped pattern was found in the morphospace, but it also showed a slight distinction between O. punctatissimus and the other species. The growth rate patterns for some structures (e.g., eye diameter, peduncle height) showed distinct allometry among the species. The same occurred for the otoliths, with distinct growth patterns in one of the shape indices (i.e., rectangularity). The otolith’s outline analysis indicated that the species are distinct groups (ANOVA, F= 4.75, p < 0.001) and highly segregated; Linear Discriminant Analysis (LDA) showed more than 94% in re-classification accuracy in such groups. Geometric morphometrics also recovered some distinction in the sulcus acusticus’ shape. Also, otoliths’ description showed slight distinctions among the species, some of these distinctions can be traced back to sister species – present only in the Pacific Ocean. Therefore, it was possible to confirm the morphological hypothesis by using complementary approaches. The likely external similarity in shape (mirrored in the morphospace) might have resulted from a recent ecological speciation process. Despite the appearing high similarity in species’ shape, differences in allometry may suggest a distinct use of habitat among those species; which agrees with the hypothesis of ecological speciation. Additionally, it brings light to the likelihood that each one of those species are under specific threat levels.